(untitled) (In situ, 2025)
At the site of the former Social Welfare building in the very heart of the Zadar peninsula, archaeological monitoring was carried out in April 2024 during the excavation of eight test pits, the aim of which was to examine the depth and condition of the foundations due to the renovation of the building.